Muslimah Mimicry and Cultural Adaptation in Hala Film (2019) - Nisa, Rahmatun; Farlina, Nina (Muslim English Literature, 2025)
This research examines the functions of mimicry in cultural adaptation strategy in the Muslimah or Muslim woman character in the Hala movie (2019). The study employs a qualitative research approach, analyzing the film’s narrative, dialogue, and visual elements through Homi K. Bhabha’s postcolonial theory of mimicry and Jens Eder’s theory of film character. The findings of this research are that Hala, as a Muslimah protagonist and a second-generation Pakistani Muslim Immigrant living in America, used the language, attire, behaviour, and mindset of American culture to balance the freedoms of American society. However, her imitation results in Muslim cultural ambivalence, as she is neither fully American nor entirely Muslimah Pakistani. This duality creates internal conflict, familial tensions, and an identity crisis. The study highlights mimicry as a survival strategy and a source of psychological turmoil, contributing to the broader discourse on second-generation Muslimah immigrant identity and postcolonial studies.